-3(u+6)+5u=

Simple and best practice solution for -3(u+6)+5u= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(u+6)+5u= equation:


Simplifying
-3(u + 6) + 5u = 0

Reorder the terms:
-3(6 + u) + 5u = 0
(6 * -3 + u * -3) + 5u = 0
(-18 + -3u) + 5u = 0

Combine like terms: -3u + 5u = 2u
-18 + 2u = 0

Solving
-18 + 2u = 0

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 2u = 0 + 18

Combine like terms: -18 + 18 = 0
0 + 2u = 0 + 18
2u = 0 + 18

Combine like terms: 0 + 18 = 18
2u = 18

Divide each side by '2'.
u = 9

Simplifying
u = 9

See similar equations:

| 5x-5=25x+3 | | -5.7a+6.2=-12.61 | | 13y^2+216y-36=0 | | 2.5+.075P=1P | | y^2-11y+32=2 | | 3(2n-1)=(2n+6)+1 | | (4a-5)=(2a-3) | | -9x-4=7x-16 | | y+5=0.2y+4.4 | | x+6-340+64=570 | | 10n=18n | | X+x^2-58=128 | | 8(2)-2x=46 | | 0.9x-2.9=0.7 | | 5(-w-2z)-6(-7z+5w)= | | 2x-5=+7 | | 22.3-3u=3.1 | | 42x-13x-30x=46 | | 8x=4x+44 | | (5k-25)-(6k+2)+7= | | -7x-4=-6x-8 | | 0.50t+3=1 | | 5y+5z=15 | | 5x+2=7+4x | | 6+4x=6x-8x-2 | | -4w-6(4x-4w)+3x= | | 3a+b-20=a-4b+42 | | 5(7x+2)-3=35x+7 | | -.5x+4=-2 | | 7w-(-z+6w)+5z= | | 150+(4n)=10n | | 4y-6+y+37=5y+40-3y |

Equations solver categories